If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + -4) = 7(2x + -3) Reorder the terms: 5(-4 + 3x) = 7(2x + -3) (-4 * 5 + 3x * 5) = 7(2x + -3) (-20 + 15x) = 7(2x + -3) Reorder the terms: -20 + 15x = 7(-3 + 2x) -20 + 15x = (-3 * 7 + 2x * 7) -20 + 15x = (-21 + 14x) Solving -20 + 15x = -21 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -20 + 15x + -14x = -21 + 14x + -14x Combine like terms: 15x + -14x = 1x -20 + 1x = -21 + 14x + -14x Combine like terms: 14x + -14x = 0 -20 + 1x = -21 + 0 -20 + 1x = -21 Add '20' to each side of the equation. -20 + 20 + 1x = -21 + 20 Combine like terms: -20 + 20 = 0 0 + 1x = -21 + 20 1x = -21 + 20 Combine like terms: -21 + 20 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1
| n+4=1-n | | 3(x+4)+7=3x+19 | | (x+745)+x+(x-301)=6360 | | (3x+2)=(4x-3) | | 62.9296(x)+(64.9278)(1-x)=63.546 | | 3(x+7)+4=3x+3 | | z^2-(1+i)z+(2+2i)=0 | | 5v+11b=622 | | -10+9p=-2 | | 2541654654xys=11 | | 3(x+7)+4=x+3 | | 33=-3(-3x-2) | | =234 | | 13+3x=-39+25x | | 2(x-5)=4x+8 | | z+1.5=2.7 | | X-21=46 | | 2s-8p=14 | | 3x^2=4-6x | | 7x^2+75=0 | | x^2-6x*8=0 | | x+0.75x=240.26 | | -3(-2-3m)=33 | | 30x-100=20 | | x+.75x=240 | | -3m+19=-5m-15 | | 3(-2v+2)-3v=33 | | -2(-t-2)=2t-14 | | 0.13513651(56.22x+5.2)+5=54x+0.213210000001 | | 10(4x+3)=-90 | | 180X-12X*X-432=0 | | 3x-5=7(6+5x) |